The influence of structure, density and direct use benefits on the harvesting of trees in the rural village of Pikoi, Eastern Cape, South Africa - Motinyane, Teboho R (Rhodes University, Faculty of Science, Department of Environmental Science, 2002)
The people of Pikoli in the Peddie district of the Eastern Cape are mostly unemployed and earn most of their income from old-age allowances. The place is remote and 'modern' amenities such as paraffin and petroleum gas are expensive. Electricity and transport are unavailable. There is heavy reliance on woody plants for fuel and for materials for construction and fencing and to some extent medicinal and ritual uses. Indigenous trees in this rural area are threatened by over-utilisation and the absence of clear government management policies. The over-utilisation of these resources is leading to deforestation. It was proposed at the beginning of this study that people who harvest trees cause similar results to the piosphere effect caused by the herbivores on the rangeland. Ecological-economic analysis was performed to find a common ground between the people's income and needs so that effective sustainable management strategies can be developed. A combination of semi-structured interviews, direct observations and ecological surveys were used to gather information about: Tree species used, and for what purpose in Pikoli; Individual tree species preference by inhabitants; Change in tree density in response to changes in utilisation intensity at varying distances away from the village; The local direct use benefits inhabitants derive from utilising indigenous tree resources. The study showed that the people of Pikoli use a variety of 23 indigenous trees and that they have marked preferences regarding the tree species they use for fuelwood and construction purposes. Although Ptaeroxylon obliquum is a highly preferred species for fuelwood and construction, its popularity can also be linked to its high relative abundance in this area. Other species such Maytenus undata and Pappea capensis are also highly preferred although they are harvested at much greater distances from thecentre of the village. Change in individual tree density in response to changes in utilisation intensity at varying distances away from the village showed clearly that a piosphere effect also applies to human harvesting. The average number of individual trees closer (1 200 m) to the village centre was 2 trees per 100 mÂ², and their numbers increase to approximately 35 trees per 100 mÂ² at a distance of about 3 000 m from the village centre. The study reports on the direct use benefits derived by the people of Pikoli from harvesting tree resources. The average total net value of trees harvested for fuelwood was R4089.09 (US$ 359.01) per household per annum. The value of tree resources harvested represents a large percentage of average households' annual income. Therefore, the economic benefits households derive from utilising tree resources are high. Indigenous tree resource use in this rural village seems to be unsustainable and the inhabitants seem to be aware of it. However, they have few alternatives. Their economic conditions do not allow them to afford alternative resources available in the formal market.
Keywords: Deforestation -- Control -- South Africa -- Eastern Cape; Deforestation -- South Africa -- Eastern Cape; Fuelwood consumption -- South Africa -- Eastern Cape; Trees -- South Africa -- Eastern Cape